Adaptive extraction method of network application signatures - Bian-qin WANG; Shun-zheng YU (Tongxin xuebao)
An adaptive application signature extraction method (AdapSig) was proposed.AdapSig firstly extracted keyword sequences from payloads of packets,and then negative examples and redundancy filter were used to generate candidate signatures.An adaptive mechanism based on self-identification rate was applied to select the final si ture.Experimental results show that application signatures extracted by AdapSig have high accuracy for various protocols.